Single and basal crop coefficients for temperate climate fruit trees, vines and shrubs with consideration of fraction of ground cover, height, and training system - López‑Urrea, Ramón (2024)
The objective of the present review article was to update the standard single (K c ) and basal (K cb ) crop coefficients published in the FAO Irrigation and Drainage Paper No. 56 (FAO56), focusing on temperate climate fruit trees (pome, stone and nut fruit trees), vines and shrubs (kiwi, hop and blue- and blackberries). Standard conditions refer to crops grown in medium to large fields, having enough fetch for non-impeding accurate use of flux measuring equipment to represent non-limiting conditions of crop evapotranspiration, ETc . Moreover, the crop needs to be managed without soil water deficit, free of pests and diseases, and must be able to reach full production under the given environmental conditions. For this purpose, more than 150 articles published over the last 25 years were reviewed. Of these, we selected 76 that refer to case studies that reporting on appropriate yield conditions, describe adequate ETc measurement and adopt the FAO reference evapotranspiration or another method closely related to it. The selection of papers to be analysed followed the same methods as the companion papers on Mediterranean woody fruit crops (Pereira et al. 2023), and on tropical and subtropical ones (Paredes et al. 2024). The literature review focused on articles that are in line with the FAO56 methodology; that is, where the grass reference evapotranspiration (ETo ) was computed with the FAO Penman–Monteith ETo , the ASCE Penman–Monteith ETo equations, or other equations whose results relate well to the former. In addition, where the crop evapotranspiration (ETc ) and/or crop transpiration (Tc ) were determined with sufficient accuracy from field observations in crops grown under standard, well- watered conditions, i.e., under pristine (i.e., non-stress cropping conditions) or eustress (i.e., “good stress”) conditions. Information collected from the selected studies included cultivar and rootstock, plant density and spacing, training system, fraction of ground cover or intercepted PAR radiation, crop height and age. Additional data were gathered on irrigation system and strategy for full or deficit irrigation. The K c and K cb values reported were recomputed and grouped according to the degree of ground cover, training system and plant density. Thus, the proposed tabulated standard K c and K cb values for initial, mid- and end-season are based on the values obtained from field observations reported in the selected papers, and on the ranges of Kc /K cb values previously tabulated, mainly in FAO56. The currently tabulated values are updated, with the aim being their use in orchard management. They should consist of the upper limit of K c /K cb application, and take into account the general awareness of water scarcity and water conservation, thus helping improve the accuracy in estimating crop water requirements and optimizing irrigation scheduling.